Respuesta :

(alternative form = 1.73205)
[tex] \sqrt{3} [/tex]

Answer: Final answer is √3.


Step-by-step explanation: Given expression 2√27+√12-3√3-2√12.

Let us simplify each of the term one by one.

2√27 = 2 √3×3×3 = 2× 3 √3 = 6 √3

√12 = √2×2×3 = 2√3

3√3 it will remain as it is.

2√12 = 2 √2×2×3 = 2×2√3 = 4√3.

So, 2√27+√12-3√3-2√12 expression would become,

6 √3 + 2√3 - 3√3 - 4√3.

Now, we can see that all radicals are like radicals.

So, we can add/subtract like radicals, we get

(6+2-3-4)√3 = 1√3.

or √3.

Therefore, final answer is √3.